(3GdJMcje aj GdVeGfGJ GdeUQajI (B/ s - (3gGfj CMeO YHO GdaJGM YWGjs; (3SejMI eUWai GdbdjhHj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2016)
(3JYO GdcaGdI GdeUQajI CcKQ GdcaGdGJ PjhkYG hGfJTGkQG , MjK jQZH GdOGFfhf YGOI ef eOjfge JbOje caGdI CMO GdHfhc dVeGf GdhaGA HOjhfge YfOeG jJNda gDdGA GdeOjfjf Yf GdSOGO , hPdc deG jJeJY Hg GdHfc ef edGAI eGdjI JHK GdWeCfjfI OGFeG ai fahS GdOGFfjf , hJNVY GdcaGdI GdeUQajI dHYV GdNUhUjI GdJi JejRgG Yf GdcaGdI GdeOfjI , hbO jJab GdOGFf hGdeOjf ai GdYbO GdCUdj Ydi TQW GdJMcje djMLHGf HehLHg fXQ GdefGRYGJ GdfGTFI Yf gPG GdYbO Yf bVGA GdOhdI djfJbd GdGNJUGU Edi GdJMcje , hYdjg fQi GKQ GdJMcje Ydi GdJRGe GdHfc Gdcajd hEecGfjI JeSc GdHfc Gdcajd HGdJMcje , hcPdc hjYO pNnWGH nGdnqVneGf UhQI ef UhQ GdVeGf GdeUQai nGnqdpJj CfTCgG GdYQa GdJLGQi (B: (3hPdc dehGLgI eJWdHGJ GdMjGI GdJLGQjI GdeYbOI hGdSQjYI (B: (3hNGUI ai eLGd GdJLGQI GdOhdjI , hgPg GdYdGbI GdWQOjI Hjf GdVeGfGJ GdeUQajI hGdJLGQI GdOhdjI JDOi Edi GdhUhd Edi YdGbI CNQi XgQJ hpGrfnJnTnQrJ ai eLGd GdJLGQI GdOhdjI ; aCUHMJ HeKGHI GdhSjdI GdfehPLjI daV GdefGRYGJ ai Pdc GdeLGd hgh nGdnqJrMpcje chSjdI daV GdefGRYGJ , MjK jXgQ hGVkMG eOi GdJbGQH hGdJLGfS Hjf gPjf GdfXGejf , aeYXe GdYbhO GdJLGQjI(B- (3NGUI GdOhdjI efgG (B- (3Jbhe Ydi pNnWGH nGdnqVneGf , hgPg GdYbhO ZGdkHG eG ojfU ajgG Ydi Cf Cj fRGY jMOK HSHHgG , aLgI nGdnqJrMpcje gi GdefhW HgG Md gPG GdfRGY (B. (3djJVM eOi YdGbI pGpqJnaGb nGdnqJrMpcje HpNnWGH nGdnqVneGf , hYdGbI TQW nGdnqJrMpcje Ydi CWQGa YbO GdCSGS hZjQg ef eSGFd GdJj jKjQhgG GdJMcjes
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GddMbhb (B- (3bSe GdbGfhf GdJLGQj (B2016.s
(3HHdjhLQGajG(B: (3UaMGJ (B295-307.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJMcjes; (3NWGHGJ GdVeGfs; (3GdJMcje (B((3TQjYI ESdGejI(B)s; (3GdcaGdI GdeUQajIs; (3GJaGb GdJMcjes; (3ZT GdeSJajOs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs